Factors influencing the prognosis of acute basilar artery occlusion patients treated endovascularly: the impact of treatment time window and preoperative symptoms - Xu, Wei; Bao, Xiang; Jiang, Fengfeng; Chen, Feng; Liu, Boxiao; Yu, Fengdan; He, Pingyou (Frontiers in Neurology, 2023)
Objective The aim of this study was to examine the factors influencing the prognosis of patients diagnosed with acute basilar artery occlusion (BAO) who receive endovascular treatment. Our particular emphasis was on the predictive implications of the time window for treatment (from symptom onset to femoral artery puncture) and preoperative symptoms for prognosis. Methods A retrospective analysis of data collected from 51 BAO patients who received endovascular treatment at the Neurosurgery Department of Jinhua Central Hospital from April 2018 to October 2021 was undertaken. The data included immediate post-interventional recanalization rates and the 90-day clinical prognoses of the patients. We used the Modified Rankin Scale (mRs) to categorize patients into two prognosis groups: a favorable prognosis group (mRs score ≤2) and an unfavorable prognosis group (mRs score >2). Preoperative symptoms were gauged using the Glasgow Coma Scale (GCS) and National Institutes of Health Stroke Scale (NIHSS) scores. A logistic regression analysis was conducted to identify risk factors affecting the prognosis of BAO patients following endovascular treatment. Results The procedure resulted in complete recanalization in all patients (100%). However, four patients (7.8%) passed away during the postoperative hospitalization period. The remaining 47 patients were followed up for 3 months. It was found that 15 patients (31.91%) had a favorable prognosis, while 32 (68.09%) had an unfavorable prognosis. It was generally observed that patients with an unfavorable prognosis had notably higher preoperative GCS and NIHSS scores (p < 0.05). Logistic regression analysis revealed that preoperative symptom severity, as indicated by NIHSS score, and treatment time window were significant prognostic risk factors for patients undergoing endovascular treatment for BAO (p < 0.05). Conclusion Endovascular intervention for BAO appears to be safe and effective, with greater likelihood of a favorable prognosis in patients treated within ≤6 h. The chances of favorable prognosis could potentially be linked to the severity of the patient's preoperative symptoms.